2011
DOI: 10.1002/ajmg.a.34024
|View full text |Cite
|
Sign up to set email alerts
|

Fanconi anemia‐like presentation in an infant with constitutional deletion of 21q including the RUNX1 gene

Abstract: We describe a newborn female with a de novo interstitial deletion of chromosome 21q21.1-22.12 including the RUNX1 gene who had developmental delay, multiple congenital anomalies, tetralogy of Fallot, anemia, and chronic thromobocytopenia requiring frequent platelet transfusions from birth. Because of her physical and hematologic abnormalities, she was tested for Fanconi anemia (FA). Lymphocytes and fibroblasts from this patient demonstrated increased chromosome breakage with exposure to the clastogen mitomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…We present a Japanese patient with a de novo 1.4‐Mb deletion at 21q22.11. To the best of our knowledge, at least 16 other reported patients share the deleted region and clinical manifestations with our patient (Table ) [Braddock and Carey, ; Orti et al, ; Albert, ; Yao et al, ; Hoyer et al, ; Beri‐Dexheimer et al, ; Shinawi et al, ; Lyle et al, ; Katzaki et al, ; Lindstrand et al, ; Byrd et al, ; Click et al, ; Melis et al, ; Thevenon et al, ; Izumi et al, ]. Among the three described regions of partial monosomy 21, regions 2 and/or 1 may produce a more severe phenotype than that produced by region 3 [Lyle et al, ; van der Crabben et al, ; Roberson et al, ].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We present a Japanese patient with a de novo 1.4‐Mb deletion at 21q22.11. To the best of our knowledge, at least 16 other reported patients share the deleted region and clinical manifestations with our patient (Table ) [Braddock and Carey, ; Orti et al, ; Albert, ; Yao et al, ; Hoyer et al, ; Beri‐Dexheimer et al, ; Shinawi et al, ; Lyle et al, ; Katzaki et al, ; Lindstrand et al, ; Byrd et al, ; Click et al, ; Melis et al, ; Thevenon et al, ; Izumi et al, ]. Among the three described regions of partial monosomy 21, regions 2 and/or 1 may produce a more severe phenotype than that produced by region 3 [Lyle et al, ; van der Crabben et al, ; Roberson et al, ].…”
Section: Discussionmentioning
confidence: 55%
“…It is possible that fetuses with full monosomy 21 die before or soon after birth [Courtens et al, ; Huret et al, ; Oegema et al, ]. In contrast, at least 45 patients with partial deletion of chromosome 21 have been reported [Braddock and Carey, ; Courtens et al, ; Theodoropoulos et al, ; Chen et al, ; Yao et al, ; Hoyer et al, ; Beri‐Dexheimer et al, ; Shinawi et al, ; Lyle et al, ; Fujita et al, ; Katzaki et al, ; Lindstrand et al, ; Oegema et al, ; Byrd et al, ; Click et al, ; Melis et al, ; Roberson et al, ; Thevenon et al, ; Izumi et al, ]. Among 21q22 microdeletion syndromes, Braddock–Carey syndrome with thrombocytopenia multiple anomalies and intellectual disability was first described in 1994 [Braddock and Carey, ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent review of other reports of RUNX1 deletions identified several suggestive of BCS. Click et al [] presented another child with phenotype consistent with Braddock–Carey syndrome and a large deletion. However, there was no evidence of ACC.…”
Section: Discussionmentioning
confidence: 99%
“…Initially referred to as either the Robin sequence thrombocytopenia syndrome or ACC thrombocytopenia syndrome, this pattern of malformation has subsequently been referred to as Braddock–Carey syndrome [Khabbaze et al, , Click et al, , Thevenon et al, , Izumi et al, , Takenouchi et al, ]. Subsequently, several reports of thrombocytopenia and developmental delay have been documented in association with deletions in the Down syndrome critical region at 21q22 [Shinawi et al, , Fujita et al, , Katzaki et al, , Byrd et al, , Click et al, , Thevenon et al, , Izumi et al, , Christensen et al, , Fukai et al, ]. At the 2011 DW Smith Workshop on Malformations and Morphogenesis, we presented new findings in the original two individuals documenting the 21q22 deletion involving RUNX1 as the potential cause of BCS [Braddock et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Translocations, small intragenic deletions or duplications, and many point mutations have been described in the literature [Michaud et al, 2002;Béri-Dexheimer et al, 2008;Shinawi et al, 2008;Jongmans et al, 2010;van der Crabben et al, 2010;Buijs et al, 2012;Cavalcante de Andrade Silva et al, 2018]. Patients show various phenotypes ranging from normal to severely affected, depending on the mechanism, and the diagnosis may be missed entirely or even misdiagnosed as Fanconi anemia [Jongmans et al, 2010;Owen, 2010;Click et al, 2011]. The product of RUNX1 is a DNA-binding protein that is part of the core-binding factor transcription complex responsible for hematopoietic stimulation and transcription of proteins related to platelet function (including PRKCQ , MYL9 , and ALOX12 ) [Godley, 2014].…”
Section: Discussionmentioning
confidence: 99%